2004
DOI: 10.1016/j.jde.2003.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Lamé equations with algebraic solutions

Abstract: In this paper we study Lame´equations L n;B y ¼ 0 in so-called algebraic form, having only algebraic functions as solution. In particular we provide a complete list of all finite groups that occur as the monodromy groups, together with a list of examples of such equations. We show that the set of such Lame´equations with ne1=2 þ Z is countable, up to scaling of the equation. This result follows from the general statement that the set of equivalent secondorder equations, having algebraic solutions and all of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
101
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(102 citation statements)
references
References 9 publications
1
101
0
Order By: Relevance
“…Γ(N )) and now, broadly speaking, the equivalence classes of Lamé equations with index n = 1 and full monodromy group isomorphic to D N are in correspondence with the zeroes of the modular forms Z N (τ ; k 1 , k 2 ), with gcd(k 1 , k 2 , N) = 1. From the analysis given in the proof of [BW,Thm. 6.1] it follows that for N ≥ 3 we have Moreover, the proof tells us that for N ≥ 3 equality in (4.2) holds if and only if the modular forms Z N (τ ; k 1 , k 2 ), where k 1 , k 2 ∈ Z and gcd(k 1 , k 2 , N) = 1, have no multiple zeroes in the upper half plane.…”
Section: Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Γ(N )) and now, broadly speaking, the equivalence classes of Lamé equations with index n = 1 and full monodromy group isomorphic to D N are in correspondence with the zeroes of the modular forms Z N (τ ; k 1 , k 2 ), with gcd(k 1 , k 2 , N) = 1. From the analysis given in the proof of [BW,Thm. 6.1] it follows that for N ≥ 3 we have Moreover, the proof tells us that for N ≥ 3 equality in (4.2) holds if and only if the modular forms Z N (τ ; k 1 , k 2 ), where k 1 , k 2 ∈ Z and gcd(k 1 , k 2 , N) = 1, have no multiple zeroes in the upper half plane.…”
Section: Applicationsmentioning
confidence: 99%
“…The counting method in [BW,Sec. 6] can also be used (as main ingredient) to obtain upper bounds for F L(n, N ) when n = 2, 3.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another approach is the Klein pullback method: Klein ([18], also [1,5,2]) showed that if the projective differential Galois group is finite, then the equation is a pullback of an equation in a finite list of well-known standard hypergeometric equations. This means that the solutions are of the form e g H(f ) where f, g ∈ k and H is a standard hypergeometric function H(x) = 2 F1([a, b], [c], x) whose parameters a, b, c appear in a finite list.…”
Section: Introductionmentioning
confidence: 99%